Optimalisasi Waktu & Biaya Pembangunan Road Elevated Pada Proyek Rancang Bangun Koperbi-Ikn Dengan Re-Engineering - Setiawan, Iwan Ari; Wibowo, Kartono; Ni’am, M. Faiqun (Jurnal Ilmiah Wahana Pendidikan, 2025)
This thesis is titled "Optimization of Time & Cost in Elevated Road Construction for Design and Build Projects KOPERBI-IKN with Re-Engineering." The background of this research focuses on the challenges within the increasingly competitive construction industry, where effectiveness, efficiency, and cost accuracy are essential for project success. The rising number of construction projects often leads to delays and discrepancies between planning and execution, impacting both time and cost. Therefore, this study aims to optimize time and costs in construction projects using a value engineering approach and descriptive quantitative analysis. The research method employed is descriptive quantitative, involving systematic steps to analyze data related to project time and costs. The results indicate fluctuations in the total project cost as the duration of working days is reduced. During the acceleration period from 150 to 143 days, there was a gradual decrease in initial and final costs; however, excessive acceleration can lead to an increase in total costs. Therefore, it is crucial to optimize acceleration by considering effective costs to achieve the desired results.